Safety and efficacy of live retrograde intrarenal surgery in patients with kindey stone: outcomes from a boutique course series which complies with the live surgery event policies - TANIDIR, YILÖREN (My University, 2023)
Background: Live surgery events (LSEs) are frequently organized for sharing the surgical experiences with surgeons at the beginning of their learning curves. The aim of this study was to investigate whether the outcomes and complication rates of patients underwent retrograde intrarenal surgery (RIRS) at LSEs are comparable with regular cases. Methods: Ten courses were organized during 2017–2022. Data of 32 patients who operated in the LSEs were 1:3 matched (for stone burden and surgeon) with the data of patients who underwent regular RIRS within the course periods at the same centers (n = 96). All courses took place in concordance with the latest LSE policies. The primary outcomes were stone-free and complication rates. Fluoroscopy and operation times were the secondary outcomes. Results: Stone-free rates of the groups were similar (84% in LSE and 79% in control group; p = 0.520). Similarly, there were no differences in complication rates (p = 0.428) and fluoroscopy time (p = 0.477). Duration of the LSE cases (82.24 ± 31.12 min) was slightly but insignificantly longer than regular cases (73.77 ± 20.89 min, p = 0.092). Moreover, guest surgeons tend to have longer operation time with statistically insignificant prolongation (74.92 ± 30.43 min for host, 89.52 ± 28.34 min for guest surgeons, p = 0.064). Conclusions: RIRS can be performed without jeopardizing operation efficiency and patient safety in LSEs. If surgeon is not familiar with operating room set-up or staff, live surgery must be performed by host surgeon to avoid extended operating time.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; Üroloji; Urology; retrograde intrarenal surgery; live surgery events; kidney stone; urolithiasis; ureteroscopy; retrograde intrarenal surgery; live surgery events; kidney stone; urolithiasis; ureteroscopy